MAPPING THE UNDEREXPLORED TERRAIN: A BIBLIOMETRIC ANALYSIS OF DIALOGIC FEEDBACK IN SENIOR HIGH SCHOOL EFL CLASSROOMS - Stefindityaningrum Gita Nurani; Bambang Widi Pratolo; Ani Susanti (Premise: Journal of English Education and Applied Linguistics, 2026)
Despite growing scholarly interest in dialogic feedback as a pedagogical strategy, no bibliometric study has systematically mapped its research landscape specifically in relation to senior high school English as a Foreign Language (EFL) classrooms (a context that remains substantially underrepresented in the global literature). This study addresses that gap by mapping research advancements and synthesizing the prospects and challenges of dialogic feedback in senior high school EFL settings. Scopus-indexed papers published between 2020 and 2026 were subjected to a combination of bibliometric analysis and qualitative thematic synthesis. After applying inclusion criteria, 368 pertinent publications were analyzed to identify prevailing research themes, publication trends, and pedagogical implications. The findings reveal a steady expansion of dialogic feedback research, with dominant concentration in higher education and technology-enhanced learning environments. Senior high school EFL contexts, particularly in non-Western countries such as Indonesia, are critically underrepresented. Enhanced student autonomy, feedback literacy, and learner engagement are identified as key opportunities, while curricular demands, time constraints, and insufficient teacher preparation represent persistent obstacles. These results indicate that more context-specific bibliometric and empirical research is needed to support effective dialogic feedback strategies in secondary EFL classrooms.